Transcriptomic Profile and Sexual Reproduction-Relevant Genes of Alexandrium minutum in Response to Nutritional Deficiency - Meng, Fan-Qiang; Song, Jun-Ting; Zhou, Jin; Cai, Zhong-Hua (Frontiers in Microbiology, 2019)
Alexandrium minutum is a typical marine toxic dinoflagellate responsible for producing paralytic shellfish poisoning (PSP) toxins. Until now, we know little about the genomic information of A.minutum, so a transcriptome study was conducted to clarify the physiological adaptations related to nutritional deficiency. Here, we performed RNA-Seq analysis to assess the gene expression patterns of A. minutum under N and P deficient conditions for 0 (control), 6, and 72 h. Main differences between the control and experimental groups were observed in hydrolase activity and fatty acid, lipid, protein, and P metabolism. Activities of photosystem I (PSI) and PSII were significantly down-regulated, and the endocytosis pathway (clathrin-dependent endocytosis) was significantly enriched under N and P stress compared with the control, indicating that A. minutum shifts its trophy pattern under N and P stress. We also identified several unigenes related to the process of sexual reproduction, including sex determination, sperm-egg recognition, sex differentiation, mating, and fertilization. Approximately 50% of the successfully annotated unigenes were differentially expressed between the short-term stimulated sample (6 h) and control (R). However, the expression level of most unigenes returned to normal levels after 72 h, indicating that N and P stress plays a limited role in the induction of sexual reproduction. Furthermore, the quantitative real-time PCR (qRT-PCR) results of the five representative sex-related unigenes were consistent with sequencing data, which confirmed the authenticity of transcriptomic analysis. Also, qRT-PCR analysis showed that the long and short form transcripts of the saxitoxin biosynthesis gene (sxtA) were down-regulated under the nutrient deficient condition compared with the control, indicating that N and P stress regulates sxtA expression. Overall, transcriptome analysis of A. minutum revealed that N and P deficiency induced responses associated with stress response, photosynthetic efficiency, toxin biosynthesis, and sexual reproduction. Our data indicate that algae change their trophic modes (to facultative mixotrophy) and related physiological reactions under stress conditions; this possibly represents an ecological adaption strategy in the algal life cycle.